Picking efficiency of cotton picker improved by unsynchronized speeds - L Carter; J Tavernetti (California Agriculture, 1960)
Picking efficiency of barbed-spindle cotton pickers was increased an average of 2.5% in a field test in the San Joaquin Valley.